LABELISASI HALAL DALAM PERLINDUNGAN KONSUMEN - Akib, Israwati (STKIP Pembangunan Indonesia Makassar, 2020)
Food is the most important basic human need, and of course in its fulfillment is part ofthe basic rights of every Indonesian people. As a country with the largest Muslim populationin Indonesia, halalism is an important indicator to be presented, especially in food products.This is what causes the importance of a food to have a halal certificate. A Muslim is not justifiedto consume food / drink before knowing halal. The purpose of this research is to find out theauthority of the MUI as an authorized institution in halal labeling and how the supervision ofhalal labeling products is carried out by the government and the community as a party thatplays an important role in conducting supervision of a product in circulation. MUI issued afatwa in terms of halal and forbiddenness of a product circulating in the community. The resultsof this study indicate that MUI as an institution authorized to set halal and haram on a product,monopolize its authority, besides that the supervision is still very low carried out by thegovernment and the community as a party that plays a role in supervising products and goodsthat are circulating in the community, so that JPH Law No.33 of 2014, cannot guarantee theprotection of consumers.Keywords: Consumer Protection; Halal Labeling; MUI.PENDAHULUAN